AN INVESTMENT STRATEGY IN PORTFOLIO SELECTION PROBLEM WITH BULLET TRANSACTION COST - SYAHRIL, E. (School of Data Science, Mathematics and Informatics, IPB University, 2003)
This paper discusses an investment strategy for a con- sumption and investment decision problem for an individual who has available a riskless asset paying ﬁxed interest rate and a risky asset driven by Brownian motion price ﬂuctuations. The individual observes current wealth when making transactions, that transac- tions incur costs, and that decisions to transact can be made at any time based on all current information. The transactions costs is ﬁxed for every transaction, regardless of amount transacted. In addition, the investor is charged a ﬁxed fraction of total wealth as management fee. The investor’s objective is to maximize the expected utility of consumption over a given horizon. The prob- lem faced by the investor is formulated in a stochastic discrete- continuous-time control problem. An investment strategy is given for ﬁxed transaction intervals.